Implementasi Model Discovery Learning Pada Materi Aplikasi Gelombang Elektromagnetik Analisis Pengotor Berbagai Minyak Goreng Sawit dengan Spektrofotometri UV-Vis - Tria Wulandari; Nirwana Nirwana; M. Lutfi Firdaus (PendIPA Journal of Science Education, 2019)
ABSTRACT[Implementation of Discovery Learning Model on Electromagnetic Wave Application Material of Various Palm Oil Impurity Analysis With Spectrophotometry UV-Vis].The aims of this study was to describe the differences between the learning outcomes of students who learn to use the learning model of Discovery Learning with students studying physics learning conventionally onwaves electromagnetic material.  The method used quasi experimental research with Pretest-Posttest Control GroupDesign research conducted at SMA Negeri 8 Lubuklinggau. Sample research used 2 classes i.e. class X.3 as a experimental class and class X.2 as a control class. Based on the results of data analysis it can be concluded that there was a difference between learning outcomes of students who learn to use the learning model of Discovery Learningwith students studying in conventional method. The data views from the average final value obtained after being given the treatment. The average value of experimental classes after being given the treatment model of learning by Discovery Learning was 76.27, while the average value of control class after being given treatment to conventional learning was 67.00.Keywords: Discovery; Learning;Electromagnetic Waves; Spectrophotometry UV-Vis.(Received August 23, 2018; Accepted March 2, 2019; Published June 18, 2019)ABSTRAKPenelitian ini bertujuan untuk menjelaskan perbedaan hasil belajar antara siswa yang belajar menggunakan model pembelajaran Discovery Learning (DL) dengan siswa yang belajar secara konvensional pada pembelajaran fisika dengan materi gelombang elektromagnetik.  Metode penelitian yang digunakan adalah penelitian eksperimen semu (Quasi Eksperimen) dengan desain penelitian Pretest-Posttest Control GroupDesign, yang dilakukan di SMA Negeri 8 Lubuklinggau. Sampel penelitian yang digunakan berjumlah 2 kelas yakni kelas X.3 sebagai kelas eksperimen dan kelas X.2 sebagai kelas kontrol. Berdasarkan hasil analisis data dapat disimpulkan bahwa terdapat perbedaan hasil belajar antara siswa yang belajar menggunakan model pembelajaran Discovery Learning (DL) dengan siswa yang belajar secara konvensional. Data tersebut dilihat dari nilai rata-rata akhir yang diperoleh setelah diberi perlakuan. Nilai rata-rata kelas eksperimen setelah diberi perlakuan dengan model pembelajaran Discovery Learning sebesar 76,27, sedangkan nilai rata-rata kelas kontrol setelah diberi perlakuan pembelajaran konvensional sebesar 67,00.Kata Kunci:Discovery; Learning; GelombangElektromagnetik; Spektrofotometri UV-Vis.